PENURUNAN KADAR DETERJEN DALAM AIR MINUM DENGAN MENGGUNAKAN SERBUK BIJI KELOR (Moringa oleifera) - Muharto Muharto (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2004)
Surabaya with 3.5 millons of population needs clean water about 10 m3/s. Large quantities of water must be supplied from Surabaya river as water source. Yet the river has polluted by detergent. It caused the clean water to contain detergent exceed the Indonesian Minister of Health Limit (0.05 mg/l detergent as LAS). In the other side moringa oleifera seed can adsorp detergent in water. Parameters, which duration influence the adsorption are detergent initial concentration, concentration and size of the seed, and time of adsorption. The adsorption process follows Freundlich isotherm adsorption model.